If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + -2p = 6 Solving 12 + -2p = 6 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + -2p = 6 + -12 Combine like terms: 12 + -12 = 0 0 + -2p = 6 + -12 -2p = 6 + -12 Combine like terms: 6 + -12 = -6 -2p = -6 Divide each side by '-2'. p = 3 Simplifying p = 3
| 3x-20=5x+6 | | 5z^3-405z=0 | | 11x^2+86x-16=0 | | 2+7z*z= | | 10.3=2t+5.8 | | 6a+2+5a+9=0 | | 0.5x+26=90 | | 2a^2+12=-60 | | -5v-(-76v)-91v=80 | | 2*7z= | | 2x=3y+13 | | X=5x+y | | u=n^2+9n-20 | | 1/4(x-3)=5 | | un=n^2+9n-20 | | 2a+12=-60 | | 19z+(-13z)+(-14z)=88 | | 7z*7z= | | 7x+10=x+120 | | 10-2(m+5)=16 | | 42g-45g+(-93)=-12 | | z*z= | | 13-6x=-38 | | 91v-16v-61v-12v-v=95 | | 16y-24=4y | | 16z-48=4z | | 51=3*3+2*3*h | | X^2+9x-3=5x-7 | | 3x-(x+1)=6m+1 | | 2m+7+3m=-33 | | 6.25y=9 | | 73-x=2x+3 |